Islamic Philanthropy Literacy through the Ramadhan Pondok Program: Zakat and Shodaqoh Education as Instruments for Economic Equality - Wiwit Mustafidah; Lilit Biati (Simfoni Ilmu Cindekia, 2026)
Activity devotion public This due to the low background understanding generation young to dimensions socio-economic from instrument Islamic philanthropy, where zakat and shodaqoh often only interpreted limited to annual ritual obligation. The purpose of this program is for increase literacy Islamic philanthropy for 822 students of SMA N 1 Genteng as well as implant awareness about the role of zakat and shodaqoh as instrument strategic in equality economy community. The approach used in activity This combine Participatory Action Research (PAR) and Project-Based Learning (PjB) were implemented through stages education interactive, discussion group concentrated, until simulation governance project​ philanthropy integrated in The Ramadhan Pondok Program series. The program's success is evaluated use qualitative data triangulation as well as analysis comparative before and after intervention. Community service results show existence shift significant paradigms on cognition and affect​ participants; understanding student transform from just compensation charitable become orientation empowerment sustainable social. Students​ proven capable practice calculation professional zakat techniques and designing distribution programs proper charity​ target. Peak from the success of this program marked with emergence initiative independent from the students for do action real raising, managing and distributing social funds in a way transparent. In conclusion, integration education Islamic economics and philanthropy through method learning based project proven to be very effective in form character concern social and intelligence financial in adolescents